New synthesis of artepillin C, a prenylated phenol, utilizing lipase-catalyzed regioselective deacetylation as the key step. Issue 12 (2nd December 2015) - Yashiro, Kazuki; Hanaya, Kengo; Shoji, Mitsuru; Sugai, Takeshi
Abstract: We have synthesized artepillin C, a diprenylated p -hydroxycinnamate originally isolated from Brazilian propolis and exhibiting antioxidant and antitumor activities, from 2, 6-diallylphenol. Replacement of the terminal vinyl with 2, 2-dimethylvinyl group by olefin cross-metathesis and subsequent transformation yielded 2, 6-diprenyl-1, 4-hydroquinone diacetate. Candida antarctica lipase B-catalyzed deacetylation in 2-propanol regioselectively removed the less hindered acetyl group to give 2, 6-diprenyl-1, 4-hydroquinone 1-monoacetate. After triflation of the liberated 4-hydroxy group, a three-carbon side chain was introduced by palladium-mediated alkenylation with methyl acrylate. Final hydrolysis of the esters furnished artepillin C. Graphical abstract: : Artepillin C, a natural prenylated phenol, was synthesized by lipase-catalyzed regioselective deacetylation on the disubstituted hydroquinone diacetate as the key step.